Using Concept Mapping to Assess Pupils’ and Students’ Awareness of the Relationship Between Organ Systems of the Human Body - Schubertová, Romana; Bednárová, Michaela (Scientia in educatione, 2018)
Recent research in science education has developed several techniques for assessing student awareness and knowledge of biological objects and phenomena. Similar to drawing, concept mapping is one of the projective techniques, yet it can also provide information about the cognitive structure formed by the pupil or student in question. The aim of this research is to describe the prevalent ideas of pupils and students about the interconnection between organ systems of the human body, and to compare these ideas. A total of 83 seventh graders at ISCED 2 level and 20 biology teacher trainees in the 1st year of the Master’s study participated in the research. The research established that pupils and students tended to emphasize nervous system in relation to the other systems, but also had a firmly rooted misconception about linking the urinary system to the digestive system. On the other hand, pupils and students proved largely unaware of the relationship between circulatory and muscular systems, even though this relationship is obvious to an expert who considers the transmission of nutrients and breathing gases. As a conclusion we provide some suggestions towards pedagogical implications that can influence the creation and transformation of the misconceptions identified throughout this project.